Frekuensi Menyikat Gigi dengan Status Karies Gigi pada Siswa SMP Negeri 1 Batipuh Kecamatan Batipuh Kabupaten Tanah Datar - Ika Ifitri; Muhammad Faisal; Eriyati Eriyati; Alsri Windra Doni (Jurnal Sehat Mandiri, 2024)
Dental caries is a disease affecting the hard tissues of teeth, impacting overall health. Brushing teeth is a crucial effort to reduce the growth of caries-causing bacteria. This study aims to analyze the relationship between tooth brushing frequency and caries status among students at SMP Negeri 1 Batipuh, Tanah Datar. A descriptive study with a cross-sectional approach was conducted in January 2023, involving 186 students as the population through saturated sampling. Data were collected using a questionnaire on tooth brushing frequency and DMF-T examination for caries status. Data analysis was performed using univariate and bivariate methods. Results indicate that 23% of students brushed their teeth once a day, 62% twice a day, and 15% three times a day. Regarding caries status, 64% had good criteria while 36% had poor criteria. Analysis revealed that students who brushed once daily had 2% with good status and 21% with poor status; those brushing twice daily had 48% good and 14% poor; and those brushing three times daily had 14% good and 1% poor. The conclusion of this study is that the most common brushing frequency is twice a day, and students with this frequency tend to have better caries status.